2017
DOI: 10.1016/j.enpol.2017.04.043
|View full text |Cite
|
Sign up to set email alerts
|

A turbine is not only a turbine: The role of social context and fairness characteristics for the local acceptance of wind power

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
68
2
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(86 citation statements)
references
References 19 publications
7
68
2
9
Order By: Relevance
“…Factors include national or regional energy market characteristics, the planning and permitting process (e.g., opportunities for informal/formal participation and consultation, information about projects and the transparency of the permitting process, trust in processes and information), governance and regulatory frameworks (e.g., national/regional/local targets, plans and policies), and trust in key actors (national/regional/local decision-makers, investors). Research shows that attitudes to wind energy are more positive if the electricity produced is used nationally and contributes to industrial development than if it is exported [14,15]. Research shows that people are concerned with a fair process.…”
Section: Literature Review and Analytical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors include national or regional energy market characteristics, the planning and permitting process (e.g., opportunities for informal/formal participation and consultation, information about projects and the transparency of the permitting process, trust in processes and information), governance and regulatory frameworks (e.g., national/regional/local targets, plans and policies), and trust in key actors (national/regional/local decision-makers, investors). Research shows that attitudes to wind energy are more positive if the electricity produced is used nationally and contributes to industrial development than if it is exported [14,15]. Research shows that people are concerned with a fair process.…”
Section: Literature Review and Analytical Frameworkmentioning
confidence: 99%
“…Mapping lead times for projects in the EU in the period 2007-2008, a study found that more than 20% of wind energy projects were delayed and nearly 20% seriously threatened due to appeals from local communities [1]. An extensive literature gives insights into why such conflicts arise, pointing to factors such as the technical characteristics of projects [2,3], environmental [4][5][6], economic [5][6][7][8][9] and societal [10][11][12][13] impacts, as well as contextual factors [14][15][16][17] and specific individual characteristics (e.g., values, preferences and beliefs) [7,8,[18][19][20]. While there is considerable knowledge about the general acceptance of wind energy technology and policies [21], there is still a need for more systematic knowledge of the relative importance of the different social acceptance factors in shaping community acceptance of specific wind energy projects.…”
Section: Introductionmentioning
confidence: 99%
“…Engineers and researchers have been continuously investigating on the improvement of wind turbines manufacturing and the reduced maintenance and operation requirements over time to push towards the development of large scale and more efficient machines (Kaldellis and Zafirakis, 2011) while Ahmed and Cameron (2014) review wind power technologies and highlight the trends of industry and challenges that these technologies will face. Williams et al (2017) show that wind power costs are expected to decrease due to technological progress but Liebe et al (2017) point out that site-specific characteristics such as landscape, circulation pattern, and seasonality that have great influences on wind stability must be properly estimated to estimate wind power. Therefore, although a considerable amount of wind power studies have been conducted (Gillenwater, 2013;Hu et al, 2013;Partridge, 2018;Shoaib et al, 2019;Thøgersen and Noblet, 2012), no single parameter can be applied universally due to the above reasons, and the estimation of turbines' power curves for different sites must be implemented and tested prior to any wind power development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A planning process which is perceived as fair can lead to greater toleration of the outcome, even if it does not fully satisfy all stakeholders (Rand and Hoen 2017). It was argued that advantages and disadvantages of a wind farm should be fairly distributed among stakeholders and also include ordinary citizens (Sonnberger and Ruddat 2017), involving participatory, procedural and distributional justice (Hall et al 2013;Liebe et al 2017). Warren and McFadyen (2010) reported that compared to privately owned wind farms, community ownership increases social acceptance of wind farms.…”
Section: Theoretical Background: Public Acceptance Of Wind Powermentioning
confidence: 99%